Human rights and religions: living together' or dying apart? A critical assessment of the dissenting opinion in S.A.S. v. France and the notion of living together' - Tsevas, Christos (Religion, state & society, 2017)
As universalism and pluralism collide when law and religion meet, is freedom of religion balanced between the universality of human rights and the religious particularities of states? To reach an answer, a thorough analysis of the ECtHR judgement S.A.S. v. France is presented, including the joint partly dissenting opinion of Judges Nussberger and Jäderblom. I focus on the notion of living together' when interpreting the majority and dissenting opinions in accordance with the nexus of human rights and religions. A second aim focuses on the use of comparative and international law in clarifying the notion of European consensus, and the way this argument is reflected in case-law and legal reasoning in one of the most discussed and controversial decisions of the ECtHR.